Perancangan Kampanye Cara Pintar dalam Berhemat Listrik Prabayar - Setyo, Sutikno Try; Iswandi, Heri; Yulius, Yosef (Jurnal Seni, Desain dan Budaya)
AbstractGovernment innovation by presenting prepaid electricity services or better known as